Low-ruthenium rutile solid solution oxide, preparation method and application in electrocatalysis field
Patent Information
- Application Number
- CN202610864788.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-16
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-06-16
AI Technical Summary
申请号202311498486.1的发明专利提供了一种钌基固溶体氧化物催化剂、制备方法及应用,该方法需要在载体表面生长、负载钌基固溶体催化剂,负载量难以精准调控
首先,本发明首先提供了一种金红石固溶体氧化物,产率高达96%,且具有较高的催化活性和稳定性。上述材料的核心催化剂位点为Ru-O-M的不对称共价键,优化对含氧中间体的吸脱附作用及反应路径,避免晶格氧的参与,显著提升催化剂的活性和稳定性。
Smart Images

Figure CN122406298B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrocatalytic materials technology, specifically relating to a low-ruthenium rutile solid solution oxide, its preparation method, and its application in the field of electrocatalysis. Background Technology
[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
[0003] Solid solution catalysts can modulate the bulk electronic structure of catalysts, improve the formation and transformation behavior of catalytic reaction intermediates, and enhance the intrinsic activity of catalysts. Therefore, exploring novel solid solution catalysts is a very necessary and meaningful task. Hydrogen energy, as a new type of clean energy source for national strategy, is gradually being transformed into a new type of productive force. Among them, proton exchange membrane electrolyzer (PEMWE) hydrogen production technology is developing rapidly, but it is limited by the requirements for high activity, acid resistance, and durability of anode catalysts. Currently, only the scarce precious metal iridium catalyst can meet the requirements, which greatly restricts the large-scale deployment of PEMWE. Therefore, the development of novel anode catalysts is imminent. Compared with iridium, ruthenium has relatively abundant reserves, and its oxides have intrinsic OER catalytic activity far exceeding that of iridium-based catalysts, making it one of the best candidates to replace iridium-based catalysts and reduce the cost of PEMWE. Ruthenium-based ruthenium solid solution catalysts achieve precise control of electronic structure by uniformly doping ruthenium atoms with other metal atoms at the lattice scale to form a homogeneous solid solution structure. This effectively reduces the reaction energy barrier of catalytic intermediates, while suppressing excessive oxidation and dissolution of ruthenium species, significantly improving the catalyst's stability in acidic environments. This solves the core problem of structural collapse and active site loss in traditional ruthenium-based catalysts under PEMWE conditions, demonstrating broad application potential in PEMWE water electrolysis. Research shows that ruthenium-based solid solutions can form an "electronic buffer" effect by constructing asymmetric Ru-OM bonds, or suppress lattice oxygen participation by controlling the reaction pathway, achieving a synergistic improvement in catalytic activity and stability. Some ruthenium-based solid solution catalysts can operate stably for hundreds or even thousands of hours at industrial-grade current densities with extremely low degradation rates. Meanwhile, due to their excellent acid corrosion resistance, ruthenium-based catalysts also have broad application prospects in the positive electrode of acidic zinc-air batteries. Compared with single-alkaline ZABs, acid-base zinc-air batteries have higher discharge voltages and greater application value.
[0004] Despite the significant advantages of ruthenium-based solid solution catalysts, their preparation technology still faces numerous unresolved problems, severely limiting their industrial application. Among existing preparation methods, the ion exchange method struggles to precisely control the solid solution content of the added element in the catalyst, while the support-supported method requires pretreatment of the support and has limited loading capacity. Therefore, using organometallic polymers can quantitatively control the metal content of the added element in the solid solution, optimize the catalyst's pore structure, and improve its activity and stability. Patent application number 202311498486.1 provides a ruthenium-based solid solution oxide catalyst, its preparation method, and its application. This method requires growing and loading the ruthenium-based solid solution catalyst on a support surface, and the loading capacity is difficult to precisely control. The article "Acid-stable ruthenium-based solid solution for oxygen evolution inproton exchange membrane electrolyzers" reports a two-step method for preparing ruthenium-based solid solution catalysts: immersing the precursor in a ruthenium solution. This method also struggles to precisely control the ruthenium content.
[0005] Therefore, this invention suggests that by precisely controlling the solid solution content of the metal-organic polymer through the precursor and optimizing the crystal structure and pore structure of the catalyst through the annealing derivatization process, it is more beneficial to obtain anode catalysts with high activity, acid corrosion resistance, and long-term stability, which have high economic value. Summary of the Invention
[0006] To address the shortcomings of the prior art, the present invention provides the following technical solution: In a first aspect, a low-ruthenium ruthenium solid solution oxide is provided, wherein the composition of the solid solution oxide is as follows: Ru x M 1-x O2, x = 0.006~0.25, where M is one or more of Ti, Cr, Mn, Co, and Ce; its XRD diffraction is in 2 θ Characteristic peaks are present at angles of 28.1±0.2°, 35.1±0.2°, 40.2±0.2° and 54.4±0.2°; The solid solution oxide consists of nanoparticles with a particle size of 3.0–11.5 nm and a specific surface area of 36.2–225.7 cm². - 3 g -1 .
[0007] In the solid solution oxide described in the first aspect above, the characteristic peak positions correspond to the (110), (101), (200) and (211) crystal planes of the rutile phase, respectively, indicating that Ru and M form a single rutile-type solid solution oxide, which is different from the prior art in which only the metal oxides are mixed.
[0008] Secondly, a method for preparing the low-ruthenium rutile solid solution oxide described in the first aspect is provided, the method comprising the following steps: S1. Precursor preparation: Ruthenium salt, metal salt containing element M, benzoic acid ligand, and surfactant are added to an organic solvent and dissolved evenly, and then subjected to a solvothermal reaction to obtain the precursor; S2. Precursor annealing: The precursor obtained in S1 is annealed in an air atmosphere to obtain the precursor.
[0009] In step S1: The metal salts referred to herein are one or more of titanium salts, chromium salts, manganese salts, cobalt salts, and cerium salts; the ruthenium salts and metal salts mentioned above are preferably inorganic salts, and more preferably inorganic acid salts, such as chloride salts, nitrate salts, or sulfate salts. When the metal salts are mixtures, the types of metal elements mixed are two or more, and the different metal elements can be mixed in equal or non-equal proportions.
[0010] The benzoic acid ligands mentioned above are selected from terephthalic acid, nitroterephthalic acid, and aminoterephthalic acid. In one embodiment verified by the present invention, the benzoic acid ligand is nitroterephthalic acid; wherein, the benzoic acid is a bidentate carboxylic acid ligand, which coordinates with metal ions through the carboxyl group (-COOH) to form a porous framework structure; the metal salt provides the metal ion as the coordination center to form a coordination polymer with the ligand.
[0011] The surfactant is selected from one or a mixture of several of the following: polyvinylpyrrolidone (PVP), urea, citric acid (CA), sodium dodecyl sulfate (SDS), hexadecyltrimethylammonium bromide (CTAB), carboxymethyl cellulose (CMC), and polyvinyl alcohol (PVA).
[0012] The organic solvent is one or a combination of N,N-dimethylformamide, ethylene glycol, isopropanol, and N,N-dimethylacetamide (DMAc).
[0013] The dosage ratio of the ruthenium salt, metal salt, benzoic acid ligand, surfactant, and organic solvent is 0.01~0.1 mmol : 0.2~1 mmol : 0.4~1.5 mmol : 0.75~1 g : 35~45 mL. Within the above dosage range, the metal salt can be a mixture of one or more metal salts. When the metal salt is a mixture, the mixed metal elements are two or more, and the different metal elements can be mixed in equal or non-equal proportions.
[0014] The temperature of the solvothermal reaction is 120~220°C, and the reaction time is 6~24 hours.
[0015] In one embodiment of step S1 above, the ruthenium salt is ruthenium chloride, the metal salt is titanium oxysulfate, and the molar ratio of ruthenium chloride to titanium oxysulfate is 0.15:0.9~1.1.
[0016] In another embodiment, the metal salt is a mixture of cobalt nitrate and cerium nitrate, in which case the molar ratio of ruthenium chloride to the metal salt is 0.01:0.18~0.22.
[0017] In another embodiment, the metal salt is a mixture of chromium nitrate and manganese nitrate, in which case the molar ratio of ruthenium chloride to the metal salt is 0.1:0.33~0.37.
[0018] In step S2: The annealing temperature is 250~700°C, and the annealing time is 2~10 hours. In one feasible embodiment, the above gas-solid reaction is carried out in a muffle furnace at a heating rate of 0.2~10°C / min, and the reaction is completed by natural cooling to obtain the low-ruthenium rutile solid solution oxide.
[0019] Thirdly, the application of the low-ruthenium ruthenium solid solution oxide described in the first aspect in the field of electrocatalysis is provided.
[0020] The low-ruthenium rutile solid solution oxide described in this invention can be used as an electrocatalyst for oxygen evolution reaction in acidic, neutral or alkaline systems and as a positive electrode for metal-air batteries. It can be applied as an anode catalytic material in proton exchange membrane electrolyzers, anion exchange membrane electrolyzers, metal-air batteries, photoelectric water splitting devices, and carbon dioxide electrolysis reduction devices. It can also be used to prepare core functional materials for electrochemical devices such as catalytic inks, membrane electrodes, and gas diffusion composite electrodes.
[0021] Furthermore, the low-ruthenium rutile solid solution oxide is used to prepare OER catalysts; even further, it is used as an anode OER catalyst for proton exchange membrane electrolyzers (PEMWE), an OER catalyst for electrochemical testing of three-electrode systems, or a cathode material for rechargeable zinc-air batteries or aluminum-air batteries.
[0022] Compared with the prior art, the beneficial effects of the present invention are: Firstly, this invention provides a rutile solid solution oxide with a yield as high as 96% and exhibiting high catalytic activity and stability. The core catalyst site of the above material is the asymmetric covalent bond of Ru-OM, optimizing the adsorption-desorption of oxygen-containing intermediates and the reaction pathway, avoiding the participation of lattice oxygen, and significantly improving the activity and stability of the catalyst.
[0023] Secondly, the present invention also provides a method for preparing the above-mentioned rutile solid solution oxide. This method is simple, does not require pretreatment of the carrier, is easy to operate, has controllable composition, and has low preparation cost. The method has good scalability and can be applied on a large scale.
[0024] Furthermore, this invention also provides the application of the above-mentioned rutile solid solution oxide in the field of electrocatalysis. As an electrocatalytic anode material, the above-mentioned material has a significantly improved lifespan and significantly improves the performance of water electrolysis. Attached Figure Description
[0025] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.
[0026] Figure 1 The XRD patterns of the low-ruthenium ruthenium solid solution oxides in Examples 1-4 are shown. Figure 2 The LSV curves of the low ruthenium rutile solid solution oxides in Examples 1-4 are shown. Figure 3 SEM image of the low-ruthenium ruthenium solid solution oxide in Example 3; Figure 4 The CP curves are for the low-ruthenium ruthenium solid solution oxide in Example 3. Detailed Implementation
[0027] It should be noted that the following detailed description is illustrative and intended to provide further explanation of the invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0028] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0029] In the context of this invention, the word "comprising" is considered to mean "particularly including". It should not be interpreted as "consisting of only".
[0030] In the description of this invention, it should be understood that the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. The symbol " / " in this document indicates that the related objects are in an "or" relationship; for example, A / B means A or B.
[0031] In the description of embodiments of the present invention, the words "exemplary" or "for example" are used to indicate that they are examples, illustrations, or descriptions. Any embodiment or design that is described as "exemplary" or "for example" in the embodiments of the present invention should not be construed as being more preferred or advantageous than other embodiments or design options. Specifically, the use of the words "exemplary" or "for example" is intended to present the relevant concepts in a specific manner.
[0032] In the description of the embodiments of the present invention, unless otherwise stated, "a plurality of" means two or more.
[0033] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments and comparative examples.
[0034] Example 1 In this embodiment, a low-ruthenium ruthenium solid solution oxide is provided, and the preparation method of the solid solution oxide is as follows: S1. Precursor preparation: 40 mL of N,N-dimethylformamide, 0.75 g of polyvinylpyrrolidone, 100 mg of nitroterephthalic acid, 0.01 mmol of ruthenium chloride, and 0.2 mmol of metal salts (cobalt nitrate and cerium nitrate) were stirred with a magnetic stirrer with heating function until the salt solution was completely dissolved to obtain a homogeneous solution; the above solution was then placed in a polytetrafluoroethylene reactor and kept at 120°C for 24 hours. After natural cooling, the solution was washed and dried to obtain the metal complex precursor.
[0035] S2. Precursor annealing: Place the above precursor in a muffle furnace and anneal at 0.2 °C for 0 min. -1 The temperature was increased to 250°C at a certain rate, held for 10 hours, and then naturally cooled to room temperature to obtain a low-ruthenium ruthenium solid solution oxide.
[0036] The low-ruthenium ruthenium solid solution oxide prepared by the above method had a collection rate of 84%, a particle size of 10.5 nm, and a specific surface area of 225.7 cm². -3 g -1 X-ray photoelectron spectroscopy analysis revealed that the ruthenium content was 2.1 at.%, the cobalt content was 14.4 at.%, the cerium content was 16.7 at.%, and the oxygen content was 66.8 at.%.
[0037] Example 2 In this embodiment, another low-ruthenium ruthenium solid solution oxide is provided, and the preparation method of the solid solution oxide is as follows: S1. Precursor preparation: 40 mL of N,N-dimethylformamide, 0.80 g of polyvinylpyrrolidone, 120 mg of nitroterephthalic acid, 0.1 mmol of ruthenium chloride, and 0.35 mmol of metal salts (chromium nitrate and manganese nitrate) were stirred with a magnetic stirrer with heating function until the salt solution was completely dissolved to obtain a homogeneous solution; the above solution was then placed in a polytetrafluoroethylene reactor and kept at 120°C for 6 hours. After natural cooling, the solution was washed and dried to obtain the metal complex precursor.
[0038] S2. Precursor annealing: Place the above precursor in a muffle furnace and anneal at 2 °C for 2 min. -1 The temperature was increased to 350°C at a certain rate, held for 5 hours, and then naturally cooled to room temperature to obtain a low-ruthenium ruthenium solid solution oxide.
[0039] The collection rate of the aforementioned low-ruthenium ruthenium solid solution oxide was 89%, with a particle size of 3.5 nm and a specific surface area of 36.2 cm². -3 g -1 It contains 7.1 at.% ruthenium, 12.6 at.% chromium, 12.1 at.% manganese, and 68.2 at.% oxygen.
[0040] Example 3 In this embodiment, another low-ruthenium ruthenium solid solution oxide is provided, and the preparation method of the solid solution oxide is as follows: S1. Precursor preparation: 40 mL of N,N-dimethylformamide, 1.0 g of polyvinylpyrrolidone, 120 mg of nitroterephthalic acid, 0.1 mmol of ruthenium chloride, and 0.35 mmol of metal salts (titanium sulfate, chromium nitrate, manganese nitrate, and cobalt nitrate) were stirred with a magnetic stirrer with heating function until the salt solution was completely dissolved, resulting in a homogeneous solution. The solution was then placed in a polytetrafluoroethylene reactor and kept at 120°C for 6 hours. After natural cooling, the solution was washed and dried to obtain the metal complex precursor.
[0041] S2. Precursor annealing: Place the above precursor in a muffle furnace and anneal at 2 °C for 2 min. -1 The temperature was increased to 350°C at a certain rate, held for 5 hours, and then naturally cooled to room temperature to obtain a low-ruthenium ruthenium solid solution oxide.
[0042] In this embodiment, the low-ruthenium ruthenium solid solution oxide collection rate was 96%, the particle size was 5.2 nm, and the specific surface area was 107.4 cm². -3 g -1It contains 5.2 at.% ruthenium, 5.3 at.% titanium, 5.7 at.% chromium, 4.9 at.% manganese, 5.6 at.% cobalt, 5.1 at.% cerium, and 68.2 at.% oxygen.
[0043] The SEM image of the low-ruthenium ruthenium solid solution oxide obtained in this embodiment is as follows: Figure 3 As shown, its CP curve is as follows Figure 4 As shown.
[0044] according to Figure 3 The low-ruthenium rutile solid solution oxide sample was composed entirely of uniformly sized ultrafine nanoparticles, without obvious bulk crystals, impurity particles, or unreacted precursor residues, demonstrating that the solvothermal-annealing process successfully prepared a homogeneous solid solution oxide. The size distribution of individual nanoparticles ranged from 3 to 7 nm, exhibiting a slightly soft aggregated state, overlapping to form a continuous three-dimensional porous network. Numerous mesopores (2–50 nm) and macropores (>50 nm) formed by particle accumulation were observed, with a wide pore size distribution. No large-area hard agglomerations or particle sintering fusion were observed, indicating that the annealing temperature of 350°C and the holding time of 5 hours were appropriately controlled, ensuring both the integrity of the crystal structure and avoiding excessive grain growth and pore collapse caused by high temperatures.
[0045] according to Figure 4 The catalyst obtained in Example 3 was at 10 mA cm⁻¹ 2 The catalyst operated stably for 1560 hours under constant current density, far exceeding the 1000-hour baseline for industrial applications of the PEMWE anode catalyst. The three-electrode reaction potential was approximately 1.42 V vs. RHE. After 1560 hours, the potential of PEMWE only increased by about 10-15 mV, with an average decay rate of <0.01 mV / h. This decay rate is far lower than that of most reported ruthenium-based catalysts and even superior to some commercial iridium-based catalysts. Throughout the test, the curve showed no significant fluctuations, no potential spikes, and no plateau breaks, indicating that the catalyst did not experience irreversible failure phenomena such as large-scale dissolution of active sites, structural collapse, or electrode detachment.
[0046] Example 4 In this embodiment, another low-ruthenium ruthenium solid solution oxide is provided, and the preparation method of the solid solution oxide is as follows: S1. Precursor preparation: 40 mL of N,N-dimethylformamide, 0.7 g of polyvinylpyrrolidone, 300 mg of nitroterephthalic acid, 0.15 mmol of ruthenium chloride, and 1 mmol of metal salt (titanium sulfate) were stirred with a magnetic stirrer with heating function until the salt solution was completely dissolved to obtain a homogeneous solution; the above solution was then placed in a polytetrafluoroethylene reactor and kept at 220°C for 3 hours. After natural cooling, the solution was washed and dried to obtain the metal complex precursor.
[0047] S2. Precursor annealing: Place the above precursor in a muffle furnace and anneal at 10 °C for 1 minute. -1 The temperature was increased to 700°C at a certain rate, held for 2 hours, and then naturally cooled to room temperature to obtain a low-ruthenium ruthenium solid solution oxide.
[0048] In this embodiment, the low-ruthenium ruthenium solid solution oxide collection rate was 78%, the particle size was 11.5 nm, and the specific surface area was 22.3 cm². -3 g -1 It contains 3.2 at.% ruthenium, 30.2 at.% titanium, and 66.6 at.% oxygen.
[0049] Comparative Example 1 In this comparative example, a control sample is provided. The preparation method differs from that of Example 1 in that ruthenium chloride is not added in step S1 to obtain the electrocatalyst of control sample 1. The rest of the settings are the same as in Example 1. Comparative Example 2 In this comparative example, another comparative sample is provided. The preparation method differs from that of Example 3 in that the solvothermal temperature in step S1 is 380°C, while the rest of the settings are the same as in Example 3, to obtain the electrocatalyst of Comparative Sample 2.
[0050] Comparative Example 3 In this comparative example, another comparative sample is provided. The preparation method differs from that of Example 3 in that the pyrolysis temperature in the muffle furnace in step S2 is 1000°C, while the rest of the settings are the same as in Example 3, to obtain the electrocatalyst of Comparative Sample 3.
[0051] The low-ruthenium rutile solid solution oxides prepared in Examples 1-4 and Comparative Examples 1-3 were used as catalysts for the OER anode side electrode. The steps were as follows: 4 mg of the sample prepared in Example 1 was dispersed in 900 μL of anhydrous ethanol and ultrasonically dispersed until uniform. Then, 100 μL of Nafion was added and ultrasonically treated for 30 min to form an ink. 10 μL of the ink was air-dried on a glassy carbon electrode and then combined with a mercury / mercurous sulfate and platinum sheet electrode to form a three-electrode system. The LSV performance of the catalyst was tested in 0.5 M H2SO4 aqueous solution, as shown in Table 1.
[0052] The obtained ink was sprayed onto the anode side of the proton exchange membrane, and the cathode side was sprayed with a 20 wt% Pt / C catalyst as the electrode material. After adding foamed titanium gas diffusion layers on both sides, a two-electrode electrolyzer was assembled. The electrolysis performance of this electrolyzer in pure water was then tested, as shown in Table 1.
[0053] Table 1. Electrolysis performance of Examples 1-4 and Comparative Examples 1-3 Based on the experimental results shown in Table 1, the catalyst in the comparative example requires a higher electrode potential to reach 10 mAcm⁻¹. -2 Meanwhile, the assembled proton exchange membrane electrolyzer also requires a relatively high cell voltage to reach 1 A cm⁻¹. -2 Therefore, non-ruthenium solid solution oxides or excessively high formation temperatures can significantly reduce the activity and stability of catalysts.
[0054] In the examples, a low content of ruthenium and transition metals was used to form a ruthenium-type solid solution oxide. Compared with the comparative example, its high catalytic activity effectively reduced the cell voltage required for the water electrolysis reaction. In addition, the relatively high stability of the catalyst in Example 3 is closely related to its component content. The multi-metal elements provide electrons to the active metal sites during the acidic OER reaction, avoiding the over-oxidation and dissolution of the active metal, and significantly improving the stability of the catalyst.
[0055] The low-ruthenium rutile solid solution oxides prepared in Examples 1-4 and Comparative Examples 1-3 were used as the cathode materials for zinc-air batteries. The steps were as follows: 4 mg of the sample prepared in Example 1 and 0.4 mg of acetylene black were dispersed in 900 μL of anhydrous ethanol and ultrasonically dispersed until uniform. Then, 100 μL of Nafion was added and ultrasonically treated for 30 min to form ink. The prepared ink was then dropped onto carbon fiber paper (with a loading of 0.4 mg cm⁻¹). 2 A zinc-air battery was assembled using air as the positive electrode, polished zinc sheet as the negative electrode, 0.5 M H2SO4 as the positive electrolyte, and 6 M KOH and 0.2 M zinc acetate as the electrolyte, separated by a bipolar membrane. The performance of the battery was then tested, as shown in Table 2.
[0056] Table 2. Zinc-air battery performance of Examples 1-4 and Comparative Examples 1-3 Comparing the data in Table 2, it can be seen that the highly active catalyst of Example 3, which exhibits acid stability, also maintains high rate performance and stability in aqueous zinc-air batteries. Compared with the open-circuit voltage of a single alkaline zinc-air battery, which is generally less than 1.5V, the acid-base zinc-air battery has a higher open-circuit voltage. The open-circuit voltage of Example 3 reaches as high as 2.22V, significantly higher than that of ordinary alkaline zinc-air batteries, indicating high application potential. Analysis reveals that the coupling and splitting of electronic orbitals in the multi-metal solid solution catalyst improves its bulk and interfacial electronic structure, optimizes the adsorption energy of reaction intermediates, and maintains stability during continuous catalytic reactions. Its smaller particle size exposes more active sites, significantly increasing the catalytic reaction current and reducing the reaction potential.
[0057] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A low-ruthenium ruthenium solid solution oxide, characterized in that, The composition of the solid solution oxide is as follows: Ru x M 1- x O2, x = 0.0063~0.216, where M is one or more of Ti, Cr, Mn, Co, and Ce; its XRD diffraction is in 2 θ Characteristic peaks are present at angles of 28.1±0.2°, 35.1±0.2°, 40.2±0.2° and 54.4±0.2°; The preparation method of the low-ruthenium ruthenium solid solution oxide includes the following steps: S1. Precursor preparation: Ruthenium salt, a metal salt containing element M, benzoic acid ligands, and a surfactant are dissolved in an organic solvent and subjected to a solvothermal reaction to obtain the precursor; the temperature of the solvothermal reaction is 120~220°C, and the reaction time is 6~24 hours; the metal salt is one or a mixture of titanium salt, chromium salt, manganese salt, cobalt salt, and cerium salt; the ruthenium salt and the metal salt are chloride salts, nitrate salts, or sulfate salts; The benzoic acid ligand is nitroterephthalic acid; The surfactant is selected from one or a mixture of several of the following: polyvinylpyrrolidone, urea, citric acid, sodium lauryl sulfate, hexadecyltrimethylammonium bromide, carboxymethyl cellulose, and polyvinyl alcohol. The organic solvent is one or a combination of several of N,N-dimethylformamide, ethylene glycol, isopropanol, and N,N-dimethylacetamide; The dosage ratio of the ruthenium salt, metal salt, benzoic acid ligand, surfactant, and organic solvent is 0.01~0.1mmol:0.2~1mmol:0.4~1.5mmol:0.7~1g:35~45mL; S2. Precursor annealing: The precursor obtained in S1 is annealed in an air atmosphere to obtain the precursor; the annealing temperature is 250~700°C and the annealing time is 2~10 hours.
2. The low-ruthenium ruthenium solid solution oxide as described in claim 1, characterized in that, The solid solution oxide consists of nanoparticles with a particle size of 3.0–11.5 nm and a specific surface area of 36.2–225.7 cm². 2 ·g -1 .
3. The low-ruthenium ruthenium solid solution oxide as described in claim 1, characterized in that, When the metal salt is a mixture, the types of metal elements mixed are two or more, and the different metal elements are mixed in equal or non-equal proportions.
4. The application of the low-ruthenium rutile solid solution oxide according to any one of claims 1-3 in the field of electrocatalysis.
5. The application as described in claim 4, characterized in that, The low-ruthenium rutile solid solution oxide is used as an electrocatalyst for oxygen evolution reaction in acidic, neutral or alkaline systems, and is applied as an anode catalytic material in proton exchange membrane electrolyzers, anion exchange membrane electrolyzers, metal-air batteries, photoelectric water splitting devices, and carbon dioxide electrolysis reduction devices; or, it is used to prepare catalytic inks, membrane electrodes or gas diffusion composite electrodes.
Citation Information
Patent Citations
Ruthenium-based solid solution oxide catalyst, preparation method and application
CN119980301A
Ruthenium-doped cobalt metal oxide nanosheet electrocatalyst as well as preparation method and application thereof
CN120138697A
Preparation method of NiCoFeRu quaternary alloy oxide material and application of NiCoFeRu quaternary alloy oxide material as alkaline hydrogen evolution / oxygen evolution reaction electrocatalyst
CN121653746A